2019
DOI: 10.1002/admi.201900629
|View full text |Cite
|
Sign up to set email alerts
|

Directed Microwave‐Assisted Self‐Assembly of Au–Graphene–Au Plasmonic Dimers for SERS Applications

Abstract: photodetection [5,6] and photocatalysis. [7] While random aggregates of silver nano particles can result in very high enhance ment, thereby facilitating the detection of single molecules through Raman scat tering; [8] for technological applications, a greater control and reproducibility over the junction dimensions and therefore enhancements will be necessary. Past efforts include using dielectric spacers, made with SiO 2 [9,10] and Al 2 O 3 [11] of con trolled thickness, as well as graphene. [5,[12][13][14] T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 43 publications
(93 reference statements)
1
14
0
Order By: Relevance
“…The other is from the abundant rough structures on the nanorices and flakes surface. The contribution of surface roughness to near-field enhancement on a mesostructure has also been confirmed by previous experiments and simulations [71][72][73]. Numerical simulations were also performed to help visualize the enhancement contributions from gaps and rough surface.…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…The other is from the abundant rough structures on the nanorices and flakes surface. The contribution of surface roughness to near-field enhancement on a mesostructure has also been confirmed by previous experiments and simulations [71][72][73]. Numerical simulations were also performed to help visualize the enhancement contributions from gaps and rough surface.…”
Section: Resultssupporting
confidence: 69%
“…where N A is Avogadro's number, and V Analyte , d Analyte , and M Analyte were the effective volume of analyte in the laser beam, the density, and molecular weights of the related analyte (Table 2), respectively. The EFs were then estimated using Equation ( 1) for the different analytes ( [70,71]. These authors linked the large EF values to multiple enhancement contributions, and that charge transfer between the g-C 3 N 4 and the metal surface protected the Ag NPs from oxidation.…”
Section: Estimation Of Sers/serrs Enhancement Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ghosh et al showed that plasmonic dimers with subnanometer gap enabled to reach enhancement factor of 10 7 and a Rhodamine 6G (R6G) detection at the ppb level. These plasmonic nanostructures were realized by directed microwave-assisted self-assembly and segregated by a graphene monolayer [ 71 ].…”
Section: Novelties On Plasmonic and Non-plasmonic Nanomaterials Fomentioning
confidence: 99%
“…To fabricate a stable metal-nanoparticle platform, graphene oxide (GO) was used as a support for the arrangement of AuNPs. Graphene and graphene-based substrates are considered a promising material for SERS sensors owing to their large surface area and excellent molecule adsorption ability, and therefore, a number of graphene-based SERS devices have been proposed [7,[18][19][20][21][22][23][24][25][26]. In addition, GO plays a crucial role as a fluorescence quencher and molecular stabilizer that render GO-metal NPs as hybrid platforms [27].…”
mentioning
confidence: 99%